1996
DOI: 10.1111/j.1525-1446.1996.tb00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Diagnostic Work on Possible Physical Child Abuse

Abstract: The concept of diagnostic work (A. Strauss, S. Fagerhaugh, B. Suczek, & C. Wiener, 1985) is used to explore nurses' responses to potential child abuse. A total of 1,036 nurses (response rate of 67%) completed a mailed questionnaire that included open-ended qualitative-type questions about a hypothetical situation involving possible child abuse. We report their judgments regarding information presented in the hypothetical situation and additional information they requested to make the diagnosis. Nurses focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The results in this study and in previous work [1][2][3]7,9,10,[16][17][18] show how nurses' knowledge, attitudes, and experience impact their decisions about restraints. The results in this study and in previous work [1][2][3]7,9,10,[16][17][18] show how nurses' knowledge, attitudes, and experience impact their decisions about restraints.…”
Section: Discussionsupporting
confidence: 66%
“…The results in this study and in previous work [1][2][3]7,9,10,[16][17][18] show how nurses' knowledge, attitudes, and experience impact their decisions about restraints. The results in this study and in previous work [1][2][3]7,9,10,[16][17][18] show how nurses' knowledge, attitudes, and experience impact their decisions about restraints.…”
Section: Discussionsupporting
confidence: 66%
“…Nevertheless, the school nurse’s role in identifying child abusing families and in caring for them, instead of concentrating only on the child, is of central importance ( Appleton, 1994, 1996; Bekemeier, 1995). O’Toole et al . (1996 ) have also found that nurses’ resources should be directed at caring for problem families more than has been the case in nursing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PD nurses were considered well qualified and well positioned to intervene in cases of child abuse (O'Toole et al, 1996). Analysis of data indicated that, in fact, the PD nurses in both venues documented their concerns about potential or actual cases of child abuse considerably more frequently than the ED nurses.…”
Section: Different Contexts; Different Codes Of Communicationmentioning
confidence: 99%